Severe receptive language disorder in childhood—familial aspects and long-term outcomes: results from a Scottish study. Issue 7 (3rd April 2007) - Clark, Ann; O'Hare, Anne; Watson, Jocelynne; Cohen, Wendy; Cowie, Hilary; Elton, Rob; Nasir, Jamal; Seckl, Jonathan
Abstract : Background and aims: Little is known about the familial characteristics of children with severe receptive specific language impairment (SLI). Affected children are more likely to have long-term problems than those with expressive SLI but to date they have only been described as small cohorts within SLI populations. We therefore aimed to describe the clinical and familial characteristics of severe receptive SLI as defined by a rigorous phenotype and to establish whether non-word repetition showed a relationship with language impairment in these families. Methods: Cross-sectional study of children who met ICD-10 (F80.2) criteria for receptive SLI at school entry, their siblings and genetic parents with standardised measures of language and non-verbal IQ, phonological auditory memory and speech sound inventory. Results: At a mean of 6 years after school entry with a severe receptive SLI, the 58 participants had a normal mean and standard deviation non-verbal IQ, but only 3% (two) had attained language measures in the normal range. One third still had severe receptive language impairment. One third of siblings not known to be affected had language levels outside the normal range. Phonological auditory memory was impaired in most family members. Conclusion: Severe receptive SLI is nearly always associated with an equally severe reduction in expressive language skills. Language impairment in siblings may go undetected and yet they are at high risk. Family members had weak phonological auditory memory skills, suggesting that this could be a marker for language acquisition difficulties. Receptive SLI rarely resolves and trials of therapy are urgently needed.